PSYCHOLOGICAL-PEDAGOGICAL ASPECTS OF DEVELOPING PROFESSIONAL-CREATIVE COMPETENCE OF FUTURE TEACHERS (Scientific journal of the Fergana State University, 2024)
In this article, the theoretical foundations of the development of the professional-creative competence of future teachers, in particular, the current issues, are studied. Also, psychological-pedagogical aspects of developing professional-creative competence of future teachers were analyzed.